Pharmaceutical care in diabetes mellitus - Clifford, Rhonda (Curtin University, 2004)
People with diabetes mellitus are more likely to die from cardiovascular causes than those without diabetes, and modifiable risk factors, such as hyperglycaemia, dyslipidaemia and hypertension can be targeted in intervention programs to decrease this risk. In addition to tertiary care for patients with diabetes, there is a need for simple programs to be implemented in the community that allow the benefits of improved metabolic and blood pressure control to be realised more widely. Pharmaceutical care comprises the detection, prevention and solution of drug-related problems in a quantifiable form, so that outcomes of care can be easily reviewed and monitored. Previous studies of pharmaceutical care programs in patients with diabetes do not provide conclusive evidence of the benefit of pharmaceutical care. The aim of this research was to evaluate the impact of the provision of pharmaceutical care to patients with diabetes mellitus in an Australian context. In order to develop a pharmaceutical care program, the characteristics of an Australian cohort of patients with diabetes were reviewed. The Fremantle Diabetes Study (FDS), was a community-based prospective observational study of diabetes care, control and complications in a postcode-defined region of 120 097 people surrounding the port city of Fremantle in Western Australia. It was intended that the FDS annual reviews would provide important local information in order to design and implement a prospective pharmaceutical care program. A pilot pharmaceutical care program was subsequently developed for use in a diabetes outpatient clinic. This program was then modified for use in a community-based sample of type 2 diabetes mellitus patients, drawn from the FDS cohort.Demographic parameters, including ethnicity and treatment details, were reviewed at study entry for the full FDS cohort and then over time for a subset of patients that returned for four subsequent annual assessments. Insulin use was more common in patients of Southern European origin compared with the Anglo-Celt group irrespective of the level of glycaemia, at baseline. This difference persisted during subsequent follow-up but was not associated with improved glycaemic control. These findings demonstrated that there are important ethnic differences in the management of patients with type 2 diabetes mellitus. The pilot pharmaceutical care program was carried out in high-risk diabetes mellitus patients attending a hospital outpatient clinic. The patients had poor glycaemic control, dyslipidaemia, hypertension and/or were on three or more prescription medications. In the pharmaceutical care arm, a clinical pharmacist reviewed and monitored all aspects of the patients' drug therapy in collaboration with other health care professionals at six weekly intervals for six months. The control patients received usual outpatient care. Seventy-three patients were recruited into the study, of whom 48 (66%) were randomised to receive pharmaceutical care. One in six patients was taking complementary medicines. The pharmaceutical care program provided patients with important medication information that resulted in changes to drug therapy. However, the six-month program did not lead to an improvement in glycaemic control. The next phase of the study adapted the pilot hospital-based pharmaceutical care program to a community-based setting.Two hundred and two type 2 diabetes mellitus FDS patients were recruited, of whom 101 (50%) were randomised to the pharmaceutical care program, and all were followed for 12-months. There were significant reductions in risk factors associated with coronary heart disease in the case but not the control group over time, specifically glycaemic control, lipid levels, and blood pressure. Glycosylated haemoglobin fell from 7.5% to 7.0% (P<0.0001), total cholesterol fell from 5 mmol/L to 4.6 mmol/L (P<0.0001), systolic blood pressure fell from 158 mmHg to 143 mmHg (P<0.0001) and diastolic blood pressure fell from 77mmHg to 71mmHg (P<0.0001). Multiple linear regression analysis confirmed that pharmaceutical care program involvement was an independent predictor of benefit after adjustment for key variables. The 10-year coronary heart disease risk for patients without a previous coronary event was reduced by 4.6% over the 12-month study period in the pharmaceutical care group (P<0.0001), while there was no change in the controls (P=0.23). This phase of the study showed that medium-term individualised pharmaceutical care reduced vascular risk factors in a community-based cohort of patients with diabetes and that provision of a multifactorial intervention can improve health outcomes in type 2 diabetes mellitus. As part of the pharmaceutical care program, a high level of complementary medicine use was found. As a result, a study of complementary medicine use was undertaken in 351 patients from the FDS. A convenience sample of FDS patients was interviewed regarding their use of complementary medicines. A literature search was conducted to assess the potential impact of these medicines on diabetes, concomitant medications or diabetes-related co-morbidities.Eighty-three of 351 (23.6%) patients with diabetes had consumed at least one complementary medicine in the previous year and 42% (77/183) of the products potentially necessitated additional patient monitoring or could be considered potentially inappropriate for a diabetic patient. The data indicated the need for patient disclosure of complementary medicine use and adequate monitoring for complementary medicine-related adverse events, as part of the pharmaceutical care process. The pharmaceutical care model was established to provide a framework by which drug use could be improved to enhance patients' clinical and health-related quality of life outcomes. For the present study, a straightforward pharmaceutical care program was adapted from a hospital setting to a community setting, where the principal requirement was a clinical pharmacist who had completed a self-directed diabetes-training program. In this context, clinically relevant parameters improved over the course of the study period. Pharmaceutical care programs such as this can begin the process of translating the findings of large and expensive clinical trials into standard clinical practice.